2019
DOI: 10.2196/12880
|View full text |Cite
|
Sign up to set email alerts
|

Codifying Online Social Support for Breast Cancer Patients: Retrospective Qualitative Assessment

Abstract: BackgroundSocial media has emerged as the epicenter for exchanging health-related information, resources, and emotional support. However, despite recognized benefits of social media for advancing health-promoting support exchange, researchers have struggled to differentiate between the different ways social support occurs and is expressed through social media.ObjectiveThe objective of this study was to develop a fuller understanding of social support exchange by examining the ways in which breast cancer patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Nevertheless, similar to other studies on the longevity of support availability ( Mikal et al, 2019 , 2020a , 2020b ), our study showed that social media platforms were very useful immediately following the transition to staying at home, but became less useful over time. Relatively quickly—by weeks three and four—social media exchanges once viewed as motivational and community-building began to wear thin for some users.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, similar to other studies on the longevity of support availability ( Mikal et al, 2019 , 2020a , 2020b ), our study showed that social media platforms were very useful immediately following the transition to staying at home, but became less useful over time. Relatively quickly—by weeks three and four—social media exchanges once viewed as motivational and community-building began to wear thin for some users.…”
Section: Discussionsupporting
confidence: 90%
“…In the first two weeks of widespread of COVID-19 in the United States (3/8/2020–3/22/2020), we recruited individuals to participate in a weekly survey on social media use. Individuals were recruited via snowball sampling with announcements posted to several Facebook groups used in prior research studies ( Mikal et al, 2016 , 2017 , 2019 , 2020a , 2020b ).…”
Section: Methodsmentioning
confidence: 99%
“…More research is needed to understand the evolution of this medium to gain a better understanding of how social media-type interventions can be used to target age-based diseases such as cancer and how social support is expressed via social media. Previous research has indicated that these platforms as a source of support for cancer may be too general and more emotionally oriented (as opposed to focused on resources/needs) [ 33 ]. Popular social media outlets such as Facebook may also provide information that needs to be appraised for quality to ensure that it is evidence based [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated and asked feedback on 3 web-based program features that were under consideration for a web-based program at that time: live web chat, Facebook discussion group, and Articulate Storyline interactive e-learning sessions. We chose these features because of their potential to facilitate engagement with a program, provision of social support, and easy access via multiple devices (smartphones and computers) [ 29 - 32 ]. Each feature was explained and demonstrated for focus group participants, followed by probing questions about the feature’s perceived effectiveness for delivering program content and promoting cancer survivors’ program participation.…”
Section: Methodsmentioning
confidence: 99%